The relationship between formal reasoning ability and metacognitive awareness with differential calculus ability in mathematics education students - Misu, La; Salam, Mohamad; Hasnawati, Hasnawati; Arapu, La (Metaverse: Journal of Mathematics Teacher Professional Development Research, 2025)
The purpose of this study was to determine the relationship between formal reasoning ability and metacognitive awareness with the differential calculus ability of mathematics education students. The population of this study were Mathematics Education students at Halu Oleo University. The sampling technique was purposive sampling, so the sample of this study was students of the S1-Mathematics Education Study Program who programmed the Differential Calculus course, consisting of new students’ class of 2024 and old students’ class of 2021. The instruments of this study were the Formal Reasoning Ability Test adapted from the Test of Logical Thinking (TOLT), a questionnaire adopted from the Metacognitive Awareness Inventory (MAI) and a test of understanding the concept of Differential calculus. The data analysis technique used descriptive statistical analysis and inferential statistical analysis. The results of the study concluded that there was a significant relationship between Formal Reasoning Ability and Calculus Ability of New Students of Mathematics Education, with a correlation coefficient of r = 0.40; while the relationship between metacognitive awareness and Calculus Ability of New Students was not significant, with correlation coefficient r = -0.12. The relationship between Formal Reasoning Ability and Calculus Ability of Old Students of Mathematics Education was not significant, with correlation coefficient r = -0.11; while the relationship between metacognitive awareness and Calculus Ability of Old Students was significant, with correlation coefficient r = 0.43.